Neuropsychiatric manifestations among HIV-1 infected African patients receiving efavirenz-based cART with or without tuberculosis treatment containing rifampicin - Mugusi, Sabina; Burhenne, Jürgen (European journal of clinical pharmacology, 2018)
Purpose: Efavirenz-based combination antiretroviral therapy (cART) is associated with neuropsychiatric adverse events. We investigated the time to onset, duration, clinical implications, impact of pharmacogenetic variations, and anti-tuberculosis co-treatment on efavirenz-associated neuropsychiatric manifestations. Methods: Prospective cohort study of cART naïve HIV patients with or without tuberculosis (HIV-TB) co-infection treated with efavirenz-based cART. Rifampicin-based anti-tuberculosis therapy was initiated 4 weeks prior to efavirenz-based cART in HIV-TB patients. Data on demographic, clinical, laboratory, and a 29-item questionnaire on neuropsychiatric manifestations were collected for 16 weeks after cART initiation. Genotyping for CYP2B6, CYP3A5, SLCO1B1, and ABCB1 and quantification of efavirenz plasma concentration were done on the 4th and 16th week. Results: Data from 458 patients (243 HIV-only and 215 HIV-TB) were analyzed. Overall incidence of neuropsychiatric manifestations was 57.6% being higher in HIV-only (66.7%) compared to HIV-TB patients (47.4%) (p < 0.01). HIV-only patients were more symptomatic, with proportionately higher grades of manifestations compared to HIV-TB patients. Median time to manifestations was 1 week after cART initiation in HIV-only and 6 weeks after anti-TB (i.e., 2 weeks after cART initiation) in HIV-TB patients. HIV-only patients had significantly higher efavirenz plasma concentrations at 4 weeks after cART compared to HIV-TB patients. No association of sex or genotype was seen in relation to neuropsychiatric manifestations. Risk for neuropsychiatric manifestations was three times more in HIV-only patients compared to HIV-TB (p < 0.01). Conclusions: Incidence of neuropsychiatric manifestations during early initiation of efavirenz-based cART is high in Tanzanian HIV patients. Risk of neuropsychiatric manifestations is lower in HIV patients co-treated with rifampicin containing anti-TB compared to those treated with efavirenz-based cART only.